Microbial Contamination of Horse Meat from Slaughterhouses in Jeneponto Regency - Ayu Lestari; J. Junaedi (Chalaza Journal of Animal Husbandry, 2021)
This research aimed to examine the microbial contamination at horse meat from traditional slaughterhouses in Jeneponto Regency to determine the quality of safe meat for human consumption. The study was conducted with a non-experimental design and observations using survey methods. Ten slaughterhouses were selected with the purposive sampling method, where meat samples were obtained and then analyzed with the total plate count method. The result showed that all samples from 10 horse slaughterhouses have more than 1x106 CFU/gram, which did not meet the SNI requirements, presumed that the meat from horse slaughterhouses was not categorized as safe for consumption. This result indicated that horse slaughterhouses in this research need sanitation and design improvement, along with good slaughtering practices.